A phase 1, first-in-child, multicenter study to evaluate the safety and efficacy of the oncolytic herpes virus talimogene laherparepvec in pediatric patients with advanced solid tumors - Moreno, Lucas; Teira, Pierre; Croop, James M.; Gerber, Nicolas U.; André, Nicolas; Aerts, Isabelle; Gros Subias, Luis; De Wilde, Bram; Bautista, Francisco; Turpin, Brian; Kunduri, Srinivasa; Hamidi, Ali; et al. (Frontiers in Pediatrics, 2023)
Background The survival rates for pediatric patients with relapsed and refractory tumors are poor. Successful treatment strategies are currently lacking and there remains an unmet need for novel therapies for these patients. We report here the results of a phase 1 study of talimogene laherparepvec (T VEC) and explore the safety of this oncolytic immunotherapy for the treatment of pediatric patients with advanced non–central nervous system tumors. Methods T-VEC was delivered by intralesional injection at 10^6 plaque-forming units (PFU)/mL the first day followed by 10^8 PFU/mL on the first day of week 4, and every 2 weeks thereafter. The primary objective was to evaluate the safety and tolerability as assessed by the incidence of dose-limiting toxicities (DLTs). Secondary objectives included efficacy indicated by response and survival per modified immune-related response criteria simulating the Response Evaluation Criteria in Solid Tumors (irRC-RECIST). Results Fifteen patients were enrolled into two cohorts based on age: cohort A1 (n = 13) 12 to ≤ 21 years old (soft-tissue sarcoma, n = 7; bone sarcoma, n = 3; neuroblastoma, n = 1; nasopharyngeal carcinoma, n = 1; and melanoma, n = 1) and cohort B1 (n = 2) 2 to < 12 years old (melanoma, n = 2). Overall, patients received treatment for a median (range) of 5.1 (0.1, 39.4) weeks. No DLTs were observed during the evaluation period. All patients experienced at least one treatment-emergent adverse event (TEAE), and 53.3% of patients reported grade  3 TEAEs. Overall, 86.7% of the patients reported treatment-related TEAEs. No complete or partial responses were observed, and three patients (20%) overall exhibited stable disease as the best response. Conclusions T-VEC was tolerable as assessed by the observation of no DLTs. The safety data were consistent with the patients’ underlying cancer and the known safety profile of T-VEC from studies in the adult population. No objective responses were observed.